Silicon carbide ceramic as well as preparation method and application thereof
Through the sintering treatment and freeze-drying process of modified silicon particles and degreasing body, the problems of inconsistent phases and high sintering temperature of porous silicon carbide ceramic materials are solved, and the preparation of homogeneous structure and high performance ceramic materials are achieved.
Patent Information
- Application Number
- CN202510050570.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
AI Technical Summary
The existing porous silicon carbide ceramic materials are inconsistent due to oxide bonding, high sintering temperature, and are prone to problems such as cracks, surface peeling and pore blockage.
The modified silicon particles and degreased blanks are sintered, and the blank structure is controlled through the freeze-drying process, the sintering temperature is reduced, and the consistency of silicon vapor and carbon reaction is improved by graphite coating.
The homogeneous structure of silicon carbide ceramics is realized, the sintering temperature is reduced, the high temperature and corrosion resistance is improved, and the cracks, surface peeling and pore blockage in the material during use are reduced.
Smart Images

Figure CN119899047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous materials, and in particular to a silicon carbide ceramic and a preparation method and application thereof. Background Art
[0002] Porous ceramics are ceramic materials that are sintered at high temperatures and have a large number of pore structures that are interconnected and connected to the surface of the material. They have the advantages of low density, good chemical stability, high operating temperature, and wear resistance. They are widely used for filtration, separation, heat insulation, sound absorption, and catalyst carriers. Based on the pore size, porous ceramics are divided into three categories: microporous materials with a pore size of less than 2nm, mesoporous materials with a pore size between 2-50nm, and macroporous materials with a pore size greater than 50nm.
[0003] Silicon carbide with a macroporous structure can be used as a filter material for gases, liquids, and solid particles in harsh environments due to its high temperature resistance, corrosion resistance, high strength, and good thermal shock resistance. It has become one of the porous ceramics that is currently being studied and applied the most. Silicon carbide is a covalently bonded compound. When a sintering aid is added, the sintering temperature generally exceeds 2000°C, which makes the manufacturing cost of the material high. For this reason, sol-gel, nitride bonding, or clay and other oxide bonding methods are usually used to reduce the sintering temperature, thereby reducing the production cost of porous silicon carbide. Among them, oxide-bonded silicon carbide can be sintered at around 1400°C under normal pressure, so the production cost is relatively low. It is the main bonding method for porous silicon carbide products currently on the market.
[0004] However, the porous silicon carbide material is bonded with oxides, which makes the phase composition of the prepared porous silicon carbide become multiple. The silicon carbide phase and the silicon oxide phase have great differences in thermal expansion coefficient, thermal shock resistance, corrosion resistance, etc., which also causes such materials to have problems as cracks, surface peeling, pore blockage, etc. during use. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of high sintering temperature and inconsistency of phase of silicon carbide ceramics in the prior art.
[0006] In order to achieve the above object, a first aspect of the present invention provides a method for preparing a silicon carbide ceramic, the method comprising:
[0007] (1) mixing the components of the composition for preparing silicon carbide ceramics to obtain a mixed slurry, and then sequentially subjecting the mixed slurry to a molding process and a freeze-drying process to obtain a green body I;
[0008] (2) subjecting the green body I to a first sintering treatment in the presence of an inert atmosphere to obtain a green body II;
[0009] (3) in the presence of silicon particles, subjecting the green body II to a second sintering treatment to obtain silicon carbide ceramics; the silicon particles are modified silicon particles at least partially coated with a graphite layer;
[0010] The content of graphite in the modified silicon particles is 5-12wt%; the mass ratio of the modified silicon particles to the blank II is 1:0.5-1.
[0011] Preferably, the mixed slurry contains a pore-forming agent and a composition A; the volume ratio of the pore-forming agent to the composition A is 1:0.5-1;
[0012] Based on the total weight of the composition A, the composition A contains 40-60wt% of α-silicon carbide, 3-8wt% of carbon powder, 5-10wt% of a binder, 0.5-1wt% of a dispersant, and 30-50wt% of water.
[0013] Preferably, the average particle diameter of the α-silicon carbide is 1-5 μm.
[0014] Preferably, the carbon powder is selected from at least one of carbon black and graphite.
[0015] Preferably, the average particle diameter of the carbon powder is 1-10 μm.
[0016] Preferably, the average particle diameter of the pore-forming agent is 0.1-5 mm.
[0017] Preferably, the binder is selected from at least one of dextrin, gelatin, polyvinyl alcohol and polyvinyl butyral.
[0018] Preferably, the dispersant is selected from at least one of sodium tripolyphosphate, sodium hexametaphosphate and polyacrylic acid.
[0019] According to a preferred embodiment, in step (2), the conditions of the first sintering treatment include: a temperature of 800-900° C. and a time of 1.5-2.5 h.
[0020] Preferably, in step (3), the conditions of the second sintering treatment include: a temperature of 1500-1600° C. and a time of 1.5-2.5 h.
[0021] Preferably, the heating rate of the second sintering treatment is 4-6°C / min.
[0022] According to a preferred embodiment, in step (3), the modified silicon particles are prepared by an operation comprising the following steps:
[0023] S1: mixing graphite slurry with raw silicon particles to obtain a mixture I;
[0024] Based on the total mass of the graphite slurry, the graphite slurry contains 10-20wt% of graphite, 1-2wt% of a homogenizing agent, 2-5wt% of a binder, and 75-85wt% of water;
[0025] S2: Drying the mixture I to obtain the modified silicon particles.
[0026] Preferably, the mass ratio of the raw silicon particles to the graphite slurry is 1:0.4-0.8.
[0027] Preferably, the average particle diameter of the raw silicon particles is 1-3 mm.
[0028] Preferably, the homogenizing agent is selected from at least one of ethanol, sodium citrate and sodium stearate.
[0029] Preferably, the binder is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose and ammonium polyacrylate.
[0030] The second aspect of the present invention provides a silicon carbide ceramic prepared by the method described in the first aspect.
[0031] The third aspect of the present invention provides application of the silicon carbide ceramic described in the second aspect in the field of filtration.
[0032] The technical solution provided by the present invention has at least the following advantages:
[0033] The present invention adopts a modification process to sinter modified silicon particles at least partially covered with a graphite layer with a degreased green body, thereby increasing the consistency and uniformity of the reaction between silicon vapor and carbon in the green body, making silicon infiltration more complete and reducing the sintering temperature of silicon carbide ceramics; the β-silicon carbide generated by the reaction combines the silicon carbide particles, and the entire ceramic is homogeneous silicon carbide, which has excellent high temperature resistance and corrosion resistance.
[0034] After the mixed slurry is formed, the present invention uses a freezing process to quickly change the water from liquid to solid, thereby preventing the mixed slurry from stratifying and settling during long-term storage; ice will leave gaps after sublimation, which is conducive to the infiltration of gas phase silicon and the reaction of carbon in the blank. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a process flow chart of silicon carbide ceramic preparation according to a preferred embodiment of the present invention;
[0036] Figure 2 It is a silicon infiltration assembly diagram of a silicon carbide blank according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0037] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0038] As mentioned above, the first aspect of the present invention provides a method for preparing silicon carbide ceramics, the method comprising:
[0039] (1) mixing the components of the composition for preparing silicon carbide ceramics to obtain a mixed slurry, and then sequentially subjecting the mixed slurry to a molding process and a freeze-drying process to obtain a green body I;
[0040] (2) subjecting the green body I to a first sintering treatment in the presence of an inert atmosphere to obtain a green body II;
[0041] (3) in the presence of silicon particles, subjecting the green body II to a second sintering treatment to obtain silicon carbide ceramics; the silicon particles are modified silicon particles at least partially coated with a graphite layer;
[0042] The content of graphite in the modified silicon particles is 5-12wt%; the mass ratio of the modified silicon particles to the blank II is 1:0.5-1.
[0043] More preferably, the mass ratio of the modified silicon particles to the green body II is 1:0.6-0.8. The inventors found in the study that by controlling the modification process of the silicon particles to obtain modified silicon particles with a graphite layer of a specific thickness, and subjecting them to the second sintering treatment with the green body II according to the mass ratio required by the present invention, a silicon carbide ceramic with a more uniform physical phase can be obtained, and the high temperature resistance and corrosion resistance of the silicon carbide ceramic product can be significantly improved, and the problems of cracks, surface peeling, pore blockage, etc. that occur during the use of the silicon carbide ceramic can be reduced.
[0044] Preferably, the mixed slurry contains a pore former and a composition A; the volume ratio of the pore former to the composition A is 1:0.5-1;
[0045] Based on the total weight of the composition A, the composition A contains 40-60wt% of α-silicon carbide, 3-8wt% of carbon powder, 5-10wt% of a binder, 0.5-1wt% of a dispersant, and 30-50wt% of water.
[0046] Preferably, the average diameter of the α-silicon carbide particles is 1-5 μm, preferably 1-2 μm.
[0047] Preferably, the carbon powder is selected from at least one of carbon black and graphite.
[0048] Preferably, the average particle diameter of the carbon powder is 1-10 μm, preferably 1-5 μm, and more preferably 1-2 μm.
[0049] The technical solution provided by the present invention can prepare porous silicon carbide ceramics with different pore sizes by using pore formers with different diameters, which has the advantage of adjustable pore size. However, in order to obtain silicon carbide ceramics with better bending strength and better air permeability, the present invention preferably has an average particle diameter of the pore former of 0.1-5 mm, preferably 0.5-2 mm.
[0050] The present invention has no particular limitation on the specific type of the pore-forming agent, as long as it is an organic solid that can be burned to leave residual carbon. Exemplarily, the pore-forming agent is an organic solid containing only C, H and O elements, such as polystyrene balls, wood processing sawdust or rice husk powder, etc. The present invention will not be described in detail herein, and those skilled in the art should not understand this as a limitation of the present invention.
[0051] Preferably, the binder is selected from at least one of dextrin, gelatin, polyvinyl alcohol and polyvinyl butyral.
[0052] Preferably, the dispersant is selected from at least one of sodium tripolyphosphate, sodium hexametaphosphate and polyacrylic acid.
[0053] Preferably, in step (1), the operation of "mixing the components in the composition for preparing silicon carbide ceramics to obtain a mixed slurry" includes:
[0054] (11) in the presence of water, the binder and the dispersant are first stirred and mixed to obtain slurry I;
[0055] (12) subjecting the slurry I to a second stirring mixing with the α-silicon carbide and the carbon powder to obtain slurry II;
[0056] (13) The slurry II and the pore-forming agent are subjected to a third stirring mixing to obtain the mixed slurry.
[0057] Preferably, in step (11), the binder is first dissolved in water and then subjected to the first stirring and mixing operation with the dispersant.
[0058] The present invention has no particular limitation on the specific method of subjecting the mixed slurry to the molding process. Those skilled in the art can make a selection based on technical means known in the art. For example, the mixed slurry is poured into a mold and then frozen to obtain a frozen-molded solid slurry.
[0059] Preferably, the freeze-drying treatment conditions include: Freezing conditions: -30°C to -40°C, freezing for 1-3 hours, so that the water in the slurry completely changes from liquid to solid ice. Vacuum drying conditions: temperature of 30-40°C, vacuum degree of 2-10Pa, time of 10-20 hours.
[0060] According to a preferred embodiment, in step (2), the conditions of the first sintering treatment include: a temperature of 800-900° C. and a time of 1.5-2.5 h.
[0061] Preferably, in step (2), the inert atmosphere is selected from at least one of argon, nitrogen and helium.
[0062] Preferably, in step (3), the conditions of the second sintering treatment include: a temperature of 1500-1600° C. and a time of 1.5-2.5 h.
[0063] Preferably, the heating rate of the second sintering treatment is 4-6°C / min.
[0064] According to a particularly preferred embodiment, the second sintering process is performed under vacuum conditions with a vacuum degree of 2-10Pa.
[0065] like Figure 2 As shown, in some embodiments, the present invention preferably performs siliconization by a silicon particle burying process, and fills the modified silicon particles around the green body II.
[0066] According to a preferred embodiment, in step (3), the modified silicon particles are prepared by an operation comprising the following steps:
[0067] S1: mixing graphite slurry with raw silicon particles to obtain a mixture I;
[0068] Based on the total mass of the graphite slurry, the graphite slurry contains 10-20wt% of graphite, 1-2wt% of a homogenizing agent, 2-5wt% of a binder, and 75-85wt% of water;
[0069] S2: Drying the mixture I to obtain the modified silicon particles.
[0070] Preferably, the mass ratio of the raw silicon particles to the graphite slurry is 1:0.4-0.8.
[0071] Preferably, the average particle diameter of the raw silicon particles is 1-3 mm.
[0072] Preferably, the homogenizing agent is selected from at least one of ethanol, sodium citrate and sodium stearate.
[0073] Preferably, the binder is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose and ammonium polyacrylate.
[0074] The method of the present invention may also include post-processing means known in the art such as residual silicon treatment on the silicon carbide ceramic obtained by the second sintering treatment. The present invention exemplarily provides a preferred specific embodiment, which should not be understood by those skilled in the art as limiting the present invention. Exemplarily, a sandblasting machine is used to sandblast the surface of the silicon carbide ceramic, and then the sandblasted product is immersed in a 0.8-1.2 mol / L sodium hydroxide solution for 10-15 hours to remove the residual silicon inside the porous silicon carbide particles.
[0075] As mentioned above, the second aspect of the present invention provides a silicon carbide ceramic prepared by the method described in the first aspect.
[0076] As mentioned above, the third aspect of the present invention provides the application of the silicon carbide ceramics described in the second aspect in the field of filtration.
[0077] The silicon carbide ceramics prepared by the technical solution provided by the present invention have excellent high temperature resistance and corrosion resistance, as well as excellent air permeability and bending strength, and are not prone to cracks, surface peeling, and pore blockage during use.
[0078] The present invention will be described in detail below through examples. In the following implementations, unless otherwise specified, the raw materials are all commercially available, as shown in Table 1. The room temperature refers to 25±2°C.
[0079] Table 1
[0080] name Type / Performance / Parameters α-SiC particles The average particle diameter is 1-2 μm Toner Carbon black, average particle diameter 1-2 μm Binder dextrin Purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd., analytical grade gelatin Purchased from Tianjin Huasheng Chemical Reagent Co., Ltd., analytical grade Dispersants Sodium tripolyphosphate / Pore forming agent Pore Forming Agent I Polystyrene spheres, average particle diameter 1mm Pore Forming Agent II Polystyrene balls, average particle diameter 0.5mm Modified silica particles Raw silicon particles The average particle diameter is 2 mm graphite Powder, average particle diameter 5μm Homogenizer Ethanol Binder Polyvinyl alcohol, purchased from Tianjin Huasheng Chemical Reagent Co., Ltd., brand name polyvinyl alcohol 1788
[0081] Preparation Example 1
[0082] Graphite, ethanol, polyvinyl alcohol and water are mixed evenly to obtain graphite slurry; in a stirring dryer, the graphite slurry and raw silicon particles are stirred and mixed at 100 rpm for 10 minutes, and then dried at 110° C. to prepare modified silicon particles.
[0083] The types and quantities of each raw material and product parameters are listed in Table 2.
[0084] Preparation Examples 2-3 and Comparative Preparation Example 1
[0085] The process was similar to that of Preparation Example 1, except that the proportions of the raw materials were different, as shown in Table 2; modified silicon particles were prepared.
[0086] Table 2
[0087] Preparation Example 1 Preparation Example 2 Preparation Example 3 Comparative Preparation Example 1 Raw silicon particles / g 500 500 500 500 Mass ratio of raw silicon particles and graphite slurry 1:0.8 1:0.4 1:0.6 1:0.3 Graphite slurry material composition Graphite / wt% 15 20 10 12 Ethanol / wt% 1 1 2 1 Polyvinyl alcohol / wt% 3 4 3 3 Water / wt% 81 75 85 84 Modified silica particles G1 G2 G3 DG1 Graphite content in modified silicon particles / wt% 10.7 7.4 5.7 3.5
[0088] Example 1
[0089] (1) A binder, a dispersant and water were stirred and mixed at 300 rpm for 10 min to obtain slurry I; α-silicon carbide and carbon powder were added to slurry I while maintaining the rotation speed unchanged and continued to be stirred and mixed for 10 min to obtain slurry II; a pore-forming agent was then added to slurry II and stirred for 10 min to obtain a mixture slurry;
[0090] The binder is a combination of dextrin and gelatin. When used, dextrin and gelatin are first dissolved in water to obtain water-soluble dextrin (solid content 60wt%) and water-soluble gelatin (solid content 10wt%).
[0091] (2) pouring the mixture slurry into an iron mold, quickly placing it in a -40°C freezer, freezing it for 2 hours, taking the mold out of the freezer, taking out the frozen solid mixture slurry from the mold, placing it in a vacuum dryer, setting the vacuum degree to 10 Pa, the temperature to 35°C, and the drying time to 14 hours, to obtain green body I;
[0092] (3) placing the prepared green body I in a high-temperature furnace and performing a first sintering treatment (heating from room temperature to 850° C. for 2 h at a heating rate of 3° C. / min) under an argon-protected atmosphere to obtain green body II;
[0093] (4) Figure 2 As shown, the body II is loaded into a graphite furnace and filled with modified silicon particles around it; under the condition of a vacuum degree of less than 5 Pa, a second sintering treatment is carried out (heating to 1550°C at 5°C / min and keeping warm for 2 hours), and then cooled to room temperature with the furnace; the sample is taken out, and the surface of the sample is sandblasted with a sandblasting machine, and the sample is placed in a 1 mol / L sodium hydroxide solution and immersed for 12 hours to remove the residual silicon inside the silicon carbide particles, thereby obtaining silicon carbide ceramics.
[0094] The types and amounts of each raw material are listed in Table 3.
[0095] Example 2 and Example 3
[0096] A similar process to Example 1 was adopted, except that the types and amounts of the raw materials were different, as shown in Table 3, to prepare silicon carbide ceramics.
[0097] Example 4
[0098] A similar process to Example 1 is adopted, except that in step (1), the pore-forming agent I is replaced by an equal volume of the pore-forming agent II, and the rest remain unchanged, to prepare silicon carbide ceramics.
[0099] Comparative Example 1
[0100] A similar process to Example 1 was adopted, except that the modified silicon particles G1 were replaced by DG1 of equal weight, and the rest remained unchanged, to prepare silicon carbide ceramics.
[0101] Comparative Example 2
[0102] A similar process to Example 1 was adopted, except that the modified silicon particles G1 were replaced with raw silicon particles of equal weight, and the rest remained unchanged, to prepare silicon carbide ceramics.
[0103] Table 3
[0104]
[0105]
[0106] Test Example 1
[0107] The parameters and performance tests of the silicon carbide ceramics prepared in the aforementioned embodiments and comparative examples were carried out, and the results are shown in Table 4.
[0108] Bulk density and apparent porosity test method: The Archimedes drainage method is used to test the bulk density and apparent porosity of the sample.
[0109] Bending strength test method: The three-point bending strength method is used to test the bending strength of the specimen.
[0110] Air permeability test method: Use an air permeability tester to test the air permeability of the sample.
[0111] Thermal shock resistance test method: Heat the sample to 1000℃, keep it warm for 5 minutes, take it out of the furnace, and place it in the air for 5 minutes. This process is a cycle and is recorded as one time.
[0112] Corrosion resistance test method: Place the sample in high-temperature molten sodium hydroxide liquid, keep it for 24 hours, and measure the change in mass of the sample before and after.
[0113] The calculation formula is: (mass before the sample is placed - mass after the sample is placed) / mass before the sample is placed × 100%.
[0114] Table 4
[0115]
[0116] It can be seen from the above results that the sintering temperature of silicon carbide ceramics prepared by the technical solution provided by the present invention is low, the prepared silicon carbide ceramics have good phase uniformity, have better high temperature resistance and corrosion resistance, and have excellent air permeability and mechanical strength, which reduces the problems of cracks, surface peeling, pore blockage, etc. that occur in silicon carbide ceramics during use, and has better application value.
[0117] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing silicon carbide ceramics, characterized in that: The method includes: (1) mixing the components of the composition for preparing silicon carbide ceramics to obtain a mixed slurry, and then sequentially subjecting the mixed slurry to a molding process and a freeze-drying process to obtain a green body I; (2) subjecting the green body I to a first sintering treatment in the presence of an inert atmosphere to obtain a green body II; (3) in the presence of silicon particles, subjecting the green body II to a second sintering treatment to obtain silicon carbide ceramics; the silicon particles are modified silicon particles at least partially coated with a graphite layer; The content of graphite in the modified silicon particles is 5-12wt%; the mass ratio of the modified silicon particles to the blank II is 1:0.5-1.
2. The method according to claim 1, characterized in that In step (1), the mixed slurry contains a pore-forming agent and a composition A; the volume ratio of the pore-forming agent to the composition A is 1:0.5-1; Based on the total weight of the composition A, the composition A contains 40-60wt% of α-silicon carbide, 3-8wt% of carbon powder, 5-10wt% of a binder, 0.5-1wt% of a dispersant, and 30-50wt% of water.
3. The method according to claim 2, characterized in that The average particle diameter of the α-silicon carbide is 1-5 μm; And / or, the carbon powder is selected from at least one of carbon black and graphite; And / or, the average particle diameter of the carbon powder is 1-10 μm.
4. The method according to claim 2, characterized in that: The average particle diameter of the pore-forming agent is 0.1-5 mm; And / or, the binder is selected from at least one of dextrin, gelatin, polyvinyl alcohol, and polyvinyl butyral; And / or, the dispersant is selected from at least one of sodium tripolyphosphate, sodium hexametaphosphate and polyacrylic acid.
5. The method according to any one of claims 1 to 4, characterized in that: In step (2), the conditions of the first sintering treatment include: a temperature of 800-900° C. and a time of 1.5-2.5 h.
6. The method according to any one of claims 1 to 4, characterized in that: In step (3), the conditions of the second sintering treatment include: a temperature of 1500-1600° C. and a time of 1.5-2.5 h; And / or, the heating rate of the second sintering treatment is 4-6°C / min.
7. The method according to any one of claims 1 to 4, characterized in that: In step (3), the modified silicon particles are prepared by an operation comprising the following steps: S1: mixing graphite slurry with raw silicon particles to obtain a mixture I; Based on the total mass of the graphite slurry, the graphite slurry contains 10-20wt% of graphite, 1-2wt% of a homogenizing agent, 2-5wt% of a binder, and 75-85wt% of water; S2: Drying the mixture I to obtain the modified silicon particles.
8. The method according to claim 7, characterized in that The mass ratio of the raw silicon particles to the graphite slurry is 1:0.4-0.8; The average particle diameter of the raw silicon particles is 1-3 mm; And / or, the homogenizing agent is selected from at least one of ethanol, sodium citrate and sodium stearate; And / or, the binder is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose and ammonium polyacrylate.
9. Silicon carbide ceramics prepared by the method according to any one of claims 1 to 8.
10. Use of the silicon carbide ceramic according to claim 9 in the field of filtration.